Curable composition, cured product, and article

By developing a curable composition containing specific polymerizable monomers, azole compounds and other components, the problem of decreasing adhesion strength of curable adhesives in a long period of time is solved, the high-stable bonding effect is achieved in a high temperature and high humidity environment, and the corrosion resistance of the metal surface is enhanced.

CN119744274APending Publication Date: 2025-04-01DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380061090.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-17
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When using a curable composition as an adhesive, the adhesive force is prone to decrease in the long term, especially in a high temperature and high humidity environment, which affects the stability of the adhesive.

Method used

By developing a curable composition including a polymerizable monomer with a carbon-carbon double bond, a radical polymerization initiator, an azole compound, an elastomer and a reducing agent, the water absorption rate of the cured film for test formed at 23°C for 24 hours was 1.5 to 3.6%, and it contains an acidic phosphoric acid compound and a specific type of azole compound to enhance its adsorption and corrosion resistance to the metal surface.

Benefits of technology

The curable composition can effectively suppress the decrease in adhesive force and maintain long-term high adhesion, especially in a high temperature and high humidity environment, and the use of the azole compound further improves the corrosion resistance of the metal surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279499320000021
    Figure BDA0005279499320000021
  • Figure BDA0005279499320000111
    Figure BDA0005279499320000111
  • Figure BDA0005279499320000171
    Figure BDA0005279499320000171
Patent Text Reader

Abstract

A curable composition containing a polymerizable monomer having a carbon-carbon double bond, a radical polymerization initiator, an azole compound, an elastomer, and a reducing agent. The curable composition is sandwiched by two PET films and cured at 23 DEG C for 24 hours to obtain a test cured film of 50 mm * 10 mm * 1 mmt, and the water absorption when the test cured film is immersed in pure water at 23 DEG C for one week is 1.5-3.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition, a cured product and an article. More specifically, the present invention relates to a curable composition, a cured product of the curable composition and an article having the cured product. Background Art

[0002] In view of its industrial importance, curable compositions have been studied for improvement from various viewpoints. Curable compositions are used, for example, as adhesives for bonding articles to each other.

[0003] Patent Document 1 discloses a curable resin composition comprising (1) a polymerizable vinyl monomer, (2) a triazole, (3) a reducing agent consisting of one or more of a tertiary amine, a thiourea derivative, and a transition metal salt, (4) a polymerization initiator, and (5) an elastomer component. According to Patent Document 1, the curable resin composition exhibits long-term high adhesion in a high-temperature and high-humidity exposure test, and is therefore useful as an adhesive for motors.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 4020236 Summary of the invention

[0007] When the curable composition is used as an adhesive to bond metal materials, it is preferred that the decrease in adhesive strength is suppressed over a long period of time. For example, when applied to bonding of zinc-chromate plated steel sheets, a curable composition that maintains good adhesive strength over a long period of time is industrially important.

[0008] The present inventors have conducted research with the aim of providing a curable composition which can suppress a decrease in adhesive strength over a long period of time when used for bonding metal materials such as zinc-chromate plated steel sheets.

[0009] As a result of research, the present inventors have completed the invention provided below.

[0010] The present invention is as follows. 1.

[0012] A curable composition comprises a polymerizable monomer having a carbon-carbon double bond, a free radical polymerization initiator, an azole compound, an elastomer and a reducing agent, wherein:

[0013] The curable composition was sandwiched between two PET films and cured at 23°C for 24 hours to obtain a 50 mm×10 mm×1 mmt test cured film. The test cured film was immersed in pure water at 23°C for one week and had a water absorption of 1.5 to 3.6%. 2.

[0015] The curable composition according to 1., wherein

[0016] The polymerizable monomer includes a (meth)acrylic monomer. 3.

[0018] The curable composition according to 1. or 2., wherein

[0019] The polymerizable monomer includes a monofunctional (meth)acrylic monomer. 4.

[0021] The curable composition according to any one of 1. to 3., wherein

[0022] The polymerizable monomer includes epoxy (meth)acrylate. 5.

[0024] The curable composition according to any one of 1. to 4., wherein

[0025] The ratio of the monomer having two or more carbon-carbon double bonds in one molecule is 0 to 10% by mass in the entire polymerizable monomers. 6.

[0027] The curable composition according to any one of 1. to 5., wherein

[0028] The elastomer includes at least one selected from the group consisting of ABS-based resin and nitrile rubber. 7.

[0030] The curable composition according to any one of 1. to 6., further comprising an acidic phosphoric acid compound represented by the following general formula (A).

[0031] [Chemical formula 1]

[0032]

[0033] In the general formula (A),

[0034] When there are a plurality of R, each R is independently a group containing a (meth)acryloyl group,

[0035] n is 1 or 2. 8.

[0037] The curable composition according to 7., wherein

[0038] In the general formula (A), an acidic phosphoric acid compound in which n is 1 and an acidic phosphoric acid compound in which n is 2 are included. 9.

[0040] The curable composition according to any one of 1. to 8., wherein

[0041] The azole compound includes at least any one selected from the group consisting of benzotriazole and tolyltriazole. 10.

[0043] The curable composition according to any one of 1. to 9., wherein

[0044] The reducing agent comprises thiourea or a derivative thereof. 11.

[0046] The curable composition according to any one of 1. to 10., wherein

[0047] The water contact angle of the surface of the test cured film was 80 to 90°. 12.

[0049] The curable composition according to any one of 1. to 11., wherein

[0050] A 1BA type dumbbell produced by curing the curable composition at 23°C for 24 hours is used as a sample, and the elongation at break when a tensile test is performed at 23°C at a tensile speed of 5 mm / min is defined as L1 (%). A 1BA type dumbbell produced by curing the curable composition at 23°C for 24 hours is immersed in pure water at 23°C for 24 hours, taken out of the water, and then cured for 1 hour in an environment of 23°C and 50RH%, and the dumbbell is used as a sample. When the elongation at break when a tensile test is performed at 23°C at a tensile speed of 5 mm / min is defined as L2 (%), the value of L2 / L1 is 0.7 to 1.5. 13.

[0052] The curable composition according to any one of 1. to 12., wherein

[0053] The curable composition is a two-component curable composition consisting of a first component and a second component, which are mixed immediately before use.

[0054] The first agent includes the radical polymerization initiator, and the second agent includes the reducing agent. 14.

[0056] The curable composition according to any one of 1. to 13., which is used as an adhesive. 15.

[0058] A cured product of the curable composition according to any one of 1. to 14. 16.

[0060] An article comprising the solidified product described in 15.

[0061] By using the curable composition of the present invention for bonding metal materials such as zinc-chromate plated steel sheets, it is possible to suppress a decrease in adhesive strength for a long period of time. DETAILED DESCRIPTION

[0062] Hereinafter, embodiments of the present invention will be described in detail.

[0063] In the present specification, unless otherwise specified, the expression "X to Y" in the description of a numerical range means greater than or equal to X and less than or equal to Y. For example, "1 to 5 mass %" means "greater than or equal to 1 mass % and less than or equal to 5 mass %".

[0064] In the notation of groups (atomic groups) in this specification, the notation not indicating whether or not a substitution is substituted includes both groups having no substitution and groups having substitution. For example, "alkyl" includes not only alkyl groups having no substitution (unsubstituted alkyl groups) but also alkyl groups having substitution (substituted alkyl groups).

[0065] The term "(meth)acrylic acid" in this specification means a concept including both acrylic acid and methacrylic acid. The same applies to similar terms such as "(meth)acrylate".

[0066] Unless otherwise specified, the term "PET" in this specification means polyethylene terephthalate.

[0067] Unless otherwise specified, the term "organic group" in this specification means an atomic group obtained by removing one or more hydrogen atoms from an organic compound. For example, a "monovalent organic group" means an atomic group obtained by removing one hydrogen atom from any organic compound.

[0068] In this specification, "non-volatile components" refer to components that do not volatilize during curing and remain in the cured product under normal use conditions of the curable composition. Generally, components other than the solvent in the curable composition correspond to non-volatile components.

[0069] <Curable composition>

[0070] The curable composition of the present embodiment includes a polymerizable monomer having a carbon-carbon double bond, a radical polymerization initiator, an azole compound, an elastomer, and a reducing agent. As the polymerizable monomer having a carbon-carbon double bond, a polymerizable monomer having a polymerizable carbon-carbon double bond is preferred.

[0071] The curable composition was sandwiched between two PET films and cured at 23°C for 24 hours to obtain a 50 mm × 10 mm × 1 mmt test cured film. The test cured film was immersed in pure water at 23°C for one week, and the water absorption was 1.5 to 3.6%, preferably 1.8 to 3.6%, and more preferably 1.9 to 3.5%.

[0072] The above-mentioned "water absorption rate" of the cured film of the curable composition of the present embodiment is small, which means that it is difficult for water to penetrate into the cured film. Although the details are not clear, it is believed that if water penetrates between the cured film and the adherend, the adhesive force decreases. Therefore, it is believed that by using the curable composition of the present embodiment that can form a cured film that is difficult for water to penetrate for bonding metal materials, it is possible to suppress the decrease in adhesive force over time.

[0073] On the other hand, it is generally believed that a material with too low a water absorption rate also has low hydrophilicity and is difficult to adhere to oxides or hydroxides on the surface of an adherend. In view of this, in the curable composition of this embodiment, a lower limit value is set for the water absorption rate.

[0074] Furthermore, the curable composition of the present embodiment includes an azole compound. An azole compound has the property of being adsorbed on a metal surface. Therefore, it is presumed that the curable composition includes an azole compound, so that the adsorption of the cured product to the metal surface is improved, and thus the adhesion is improved.

[0075] By including the azole compound in the curable composition of the present embodiment, it is also possible to suppress the corrosion of the metal surface as the adherend. The "corrosion inhibition effect" can be further improved by appropriately adjusting the specific structure of the azole compound or the usage amount of the azole compound. The metal as the adherend is of course preferably not corroded, so it is preferably the curable composition of the present embodiment that exerts the corrosion inhibition effect in industry.

[0076] As described above, it is considered that the curable composition of the present embodiment, due to the synergistic effect of moisture hardly intruding into the cured film and the inclusion of the azole compound, suppresses the decrease in adhesive strength for a long period of time when used as an adhesive.

[0077] Incidentally, a curable composition with a small water absorption rate when making a cured product as in the present embodiment can be manufactured by using an appropriate amount of appropriate materials. Specifically, the composition of the embodiments listed below can be referred to. As a viewpoint of material selection, for example, (i) using a polymerizable monomer containing an aromatic group such as a phenyl group (preferably not substituted by a polar group), (ii) using a polymerizable monomer containing an alicyclic group such as an isobornyl group (preferably not substituted by a polar group), (iii) not using (even if used, a small amount of) a polymerizable monomer having a hydrophilic structure such as an alkylene oxide chain, (iv) by using a multifunctional polymerizable monomer to increase the crosslinking density, etc.

[0078] Hereinafter, components that can be contained in the curable composition of the present embodiment or the characteristics of the curable composition of the present embodiment will be described.

[0079] (Polymerizable monomer having a polymerizable carbon-carbon double bond)

[0080] The curable composition of the present embodiment contains a polymerizable monomer having a polymerizable carbon-carbon double bond.

[0081] Hereinafter, a polymerizable monomer having a polymerizable carbon-carbon double bond may be simply referred to as a "polymerizable monomer".

[0082] The polymerizable monomer preferably includes a (meth)acrylic monomer. That is, the polymerizable monomer preferably has a (meth)acryloyl group as a structure including a polymerizable carbon-carbon double bond.

[0083] The polymerizable monomer preferably contains a monofunctional monomer (a monomer having one polymerizable carbon-carbon double bond in one molecule). As the monofunctional monomer, a monofunctional (meth)acrylic monomer is preferred.

[0084] By mixing the polymerizable monomer mainly with the monofunctional (meth) acrylic monomer, for example, there is a tendency to improve the thermal cycling property when the curable composition is used as an adhesive. It is presumed that this is because by mixing the polymerizable monomer mainly with the monofunctional (meth) acrylic monomer, the cured product of the curable composition becomes appropriately soft.

[0085] Specifically, the ratio of the monofunctional (meth) acrylic monomer in the total polymerizable monomer is preferably 80 to 100% by mass, more preferably 80 to 97% by mass, further preferably 85 to 97% by mass, and particularly preferably 85 to 95% by mass. Incidentally, when the ratio of the monofunctional (meth) acrylic monomer in the total polymerizable monomer is not 100% by mass, the monomer used simultaneously with the monofunctional (meth) acrylic monomer may be, for example, a multifunctional (meth) acrylate monomer, preferably an epoxy (meth) acrylate listed below.

[0086] When the ratio of the monofunctional (meth) acrylic monomer in the total polymerizable monomer is large, the ratio of the multifunctional monomer (a monomer having two or more polymerizable carbon-carbon double bonds in one molecule) in the total polymerizable monomer is inevitably reduced. The polymerizable monomer preferably does not contain a multifunctional monomer, or even if it contains a small amount. Specifically, the ratio of the multifunctional monomer in the total polymerizable monomer is preferably 0 to 10% by mass, more preferably 0 to 8% by mass, and further preferably 0 to 6% by mass.

[0087] In order to obtain a cured film with low water absorption, the polymerizable monomer preferably includes a polymerizable monomer having an aromatic group such as a phenyl group (preferably not substituted by a polar group). For the same reason, the polymerizable monomer preferably uses a polymerizable monomer having an alicyclic group such as an isobornyl group (preferably not substituted by a polar group). Incidentally, these polymerizable monomers sometimes contribute to improving the durability or mechanical properties of the cured product due to the rigidity of the aromatic group or the alicyclic group.

[0088] From the viewpoint of obtaining a cured film with low water absorption, the polymerizable monomer preferably does not contain (even if contained, it is a small amount) a polymerizable monomer having a highly hydrophilic structure such as an alkylene oxide chain. Specifically, the ratio of the polymerizable monomer having an alkylene oxide chain in the entire polymerizable monomer is preferably 0 to 10% by mass, more preferably 0 to 5% by mass, and further preferably 0 to 3% by mass.

[0089] On the other hand, from the viewpoint of improving the adhesion to an adherend when the curable composition is used as an adhesive, the polymerizable monomer may contain a (meth)acrylate having a polar group such as a (meth)acrylate having a hydroxyl group.

[0090] Examples of polymerizable monomers that can be used are given below.

[0091] Linear or branched alkyl (meth)acrylate: specifically, monofunctional (meth)acrylic monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate.

[0092] When a linear or branched alkyl (meth)acrylate is used, the amount thereof is preferably 10 to 50% by mass, more preferably 20 to 45% by mass, based on the entire polymerizable monomer.

[0093] (Meth)acrylates having a hydroxyl group, in particular (meth)acrylates having a hydroxyalkyl group: specifically, monofunctional (meth)acrylic monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0094] When using the (meth)acrylate having a hydroxyl group, the amount thereof is preferably 10 to 45% by mass, more preferably 15 to 40% by mass, based on the entire polymerizable monomer.

[0095] Polymerizable monomer having an alicyclic group: specifically, monofunctional (meth)acrylic monomers such as dicyclopentenyloxyethyl (meth)acrylate, norbornene (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, cyclohexyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.

[0096] When a polymerizable monomer having an alicyclic group is used, the amount thereof is preferably 3 to 30% by mass, more preferably 5 to 20% by mass, based on the entire polymerizable monomer.

[0097] Polymerizable monomer having an aromatic group: specifically, a monofunctional (meth)acrylic monomer such as benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate.

[0098] When a polymerizable monomer having an aromatic group is used, the amount thereof is preferably 5 to 30% by mass, more preferably 5 to 20% by mass, based on the entire polymerizable monomer.

[0099] In addition to the above-mentioned polymerizable monomers (mainly monofunctional (meth) acrylic monomers), the curable composition of the present embodiment may also contain epoxy (meth) acrylate. Epoxy (meth) acrylate refers to a compound obtained by reacting all epoxy groups in an epoxy compound with (meth) acrylic acid, and has a (meth) acryloyl group. By including epoxy (meth) acrylate monomers in the polymerizable monomers, it is easy to take into account both rapid curing and stress relaxation during curing.

[0100] Epoxy (meth)acrylate may be monofunctional or polyfunctional. From the viewpoint of balancing various properties, epoxy (meth)acrylate is preferably polyfunctional, more preferably difunctional to tetrafunctional, and even more preferably difunctional. Here, n-functional means having n polymerizable carbon-carbon double bonds in one molecule.

[0101] Specific examples of epoxy (meth)acrylates include EBECRYL860, EBECRYL3200, EBECRYL3201, EBECRYL3412, EBECRYL3600, EBECRYL3700, EBECRYL3701, EBECRYL3702, EBECRYL3703, EBECRYL3708, EBECRYL3800, EBECRYL6040, and EBECRYL RDX63182 sold by DAICEL-ALLNEX LTD. and ME2100, PE210, PE250, SC6360, SC6400, PE110H, PE230, PE310, EA2235, EA2255, EA2259, and EA2280 sold by Miwon Specialty Chemical Co., Ltd. Epoxy (meth)acrylate is sold by SHIN-NAKAMURA CHEMICAL CO, LTD. and KYOEISHA CHEMICAL Co., LTD. in addition to DAICEL-ALLNEX LTD.

[0102] When epoxy (meth)acrylate is used, the amount thereof is preferably 1 to 15% by mass, more preferably 2 to 13% by mass, based on the entire polymerizable monomer.

[0103] The curable composition of the present embodiment may contain only one polymerizable monomer or may contain two or more polymerizable monomers. In consideration of the balance of various performances, the curable composition of the present embodiment preferably contains two or more polymerizable monomers.

[0104] The ratio of the polymerizable monomer in the total non-volatile components of the curable composition of the present embodiment is preferably 50 to 99% by mass, more preferably 60 to 97% by mass, and further preferably 70 to 95% by mass. By sufficiently increasing the ratio of the polymerizable monomer, sufficient curing can be achieved. On the other hand, since the ratio of the polymerizable monomer is not too large, a sufficient amount of other components can be included in the polymerizable composition, so it is easy to balance various properties.

[0105] (Free Radical Polymerization Initiator)

[0106] The curable composition of the present embodiment contains a radical polymerization initiator. The radical polymerization initiator is not particularly limited as long as it can polymerize the polymerizable carbon-carbon double bonds of the polymerizable monomer.

[0107] As the radical polymerization initiator, preferably, an organic peroxide, that is, a compound having a peroxide structure or a compound having a percarboxylic acid structure can be used.

[0108] Preferred free radical polymerization initiators include, specifically, tert-amyl peroxybenzoate (tert-amyl peroxybenzoate), tert-hexyl peroxybenzoate, tert-hexyl peroxyisopropyl carbonate, tert-amyl peroxy-3,5,5-trimethylhexanoate, tert-hexyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxybenzoate, cumene hydroperoxide, p-menthane hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene dihydroperoxide, methyl ethyl ketone peroxide, tert-butyl peroxybenzoate, and the like.

[0109] The curable composition of the present embodiment may contain only one radical polymerization initiator, or may contain two or more radical polymerization initiators.

[0110] The amount of the radical polymerization initiator used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, and even more preferably 1 to 10 parts by mass, based on 100 parts by mass of the polymerizable monomer.

[0111] (Azole compound)

[0112] The curable composition of the present embodiment contains an azole compound. Any azole compound can be used as long as it has adsorption ability to a metal surface.

[0113] Preferred examples of the azole compound include triazole compounds and tetrazole compounds, among which triazole compounds are preferred.

[0114] As the triazole compound, preferably, there can be mentioned compounds having a benzotriazole structure such as benzotriazole, methylbenzotriazole (benzotriazole in which a methyl group is substituted on the benzene ring), carboxybenzotriazole, 4,5,6,7-tetrahydrobenzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'5'-di-tert-butylphenyl)benzotriazole, and 2-(2'-hydroxy-4-octyloxyphenyl)benzotriazole. Triazole or tetrazole having no substituent can also be used.

[0115] The azole compound particularly preferably includes at least any one selected from the group consisting of benzotriazole and tolyltriazole.

[0116] The curable composition of the present embodiment may contain only one type of azole compound, or may contain two or more types of azole compounds.

[0117] From the viewpoint of balance with adsorption to the adherend, anticorrosion effect on metal materials, other properties, etc., the amount of the azole compound used is preferably 0.1 to 5 mass %, more preferably 0.2 to 4 mass %, and even more preferably 0.3 to 3 mass % in the total non-volatile components of the curable composition.

[0118] (Elastomer)

[0119] The curable composition of the present embodiment includes an elastomer. It is believed that when the curable composition of the present embodiment is used as an adhesive, the elastomer contributes to improving bonding strength. It is believed that the curable composition comprising an elastomer can absorb shrinkage stress when solidified, so the cured product is difficult to peel off from the adherend, i.e., the adhesion is good.

[0120] The type of elastomer is not particularly limited, and preferably includes (meth)acrylonitrile-butadiene-styrene resin or (meth)acrylonitrile-butadiene rubber. As the (meth)acrylonitrile-butadiene-styrene resin, preferably one or more of ABS (acrylonitrile-butadiene-styrene) resin or (meth)acrylonitrile-butadiene-styrene) polymer. As the (meth)acrylonitrile-butadiene-styrene polymer, preferably MABS (methyl methacrylate-acrylonitrile-butadiene-styrene) polymer. As the (meth)acrylonitrile-butadiene rubber, preferably acrylonitrile-butadiene rubber (nitrile rubber).

[0121] As the ABS resin, a commercial product can be used. Commercially available ABS resins include "TECHNO ABS" (TECHNO POLYMER Co., Ltd.), "UMG ABS" (UMG ABS, LTD.), "Denka ABS" (Denka Company Limited), etc. In addition, the ABS resin may be an MABS polymer also called a transparent ABS resin. Commercially available products of the MABS polymer include KANEACE (KANEKA CORPORATION), etc.

[0122] A commercially available product may be used for the nitrile rubber. For example, a product corresponding to the nitrile rubber may be appropriately selected from products sold under the product name of "Nipol" (registered trademark) by ZEON CORPORATION and used.

[0123] The curable composition of the present embodiment may contain only one elastomer or more than two elastomers. For example, the above-mentioned (meth) acrylonitrile-butadiene-styrene resin and (meth) acrylonitrile-butadiene rubber may be used simultaneously. When used simultaneously, the simultaneous use ratio is, for example, the former: the latter = 1:9 to 9:1 in terms of mass ratio, preferably the former: the latter = 2:8 to 8:2.

[0124] The amount of the elastomer used is preferably 5 to 35 parts by mass, more preferably 10 to 30 parts by mass, and even more preferably 10 to 25 parts by mass, based on 100 parts by mass of the polymerizable monomer.

[0125] (reducing agent)

[0126] The curable composition of this embodiment includes a reducing agent. Due to the action of the reducing agent, a large number of free radicals can be generated from the free radical polymerization initiator even at room temperature, and the curable composition can be cured. That is, the action of the reducing agent can achieve room temperature curing.

[0127] As the reducing agent, a known reducing agent that reacts with a radical polymerization initiator to generate a radical can be appropriately used, and specific examples thereof include tertiary amines, thiourea or derivatives thereof, and transition metal salts.

[0128] In the present embodiment, the reducing agent particularly preferably comprises thiourea or its derivatives. Specifically, thiourea or its derivatives such as vinyl thiourea, acetyl thiourea, dimethyl thiourea, tetramethyl thiourea, thioacetamide, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole can be cited. Thiourea or its derivatives have the tautomerism between the structure forming a double bond between carbon atom-sulfur atom and the structure forming a double bond between adjacent carbon atom-nitrogen atom, and each other's structure becomes equilibrium state and exists. If it contacts with free radical polymerization initiator, then gradually destroys the equilibrium state, and reacts relatively slowly with free radical polymerization initiator, so as to stably produce free radicals. Therefore, it is inferred that by using thiourea or its derivatives as reducing agent, the cured product of curable composition will not become too hard and can obtain a moderately soft cured product. This is a preferred property when the curable composition of the present embodiment is applied to adhesive.

[0129] The curable composition of the present embodiment may contain only one reducing agent, or may contain two or more reducing agents.

[0130] The amount of the reducing agent used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the polymerizable monomer. When 0.01 parts by mass or more is used, the curing speed becomes sufficiently high, and when it is 10 parts by mass or less, the storage stability becomes good.

[0131] (Acidic phosphoric acid compound)

[0132] The curable composition of the present embodiment preferably contains an acidic phosphoric acid compound represented by the following general formula (A).

[0133] According to the findings of the present inventors, it is considered that this compound contributes to further improving the adhesion when the curable composition of the present embodiment is used as an adhesive.

[0134] [Chemical formula 2]

[0135]

[0136] In the general formula (A),

[0137] When there are a plurality of R, each R is independently a group containing a (meth)acryloyl group,

[0138] n is 1 or 2.

[0139] R may be (i) a (meth)acryloyl group itself, or (ii) a group in which a (meth)acryloyl group is bonded to an oxygen atom via a divalent linking group.

[0140] To explain (ii) more specifically, R may be a group represented by R'-L-, wherein R' is a (meth)acryloyl group, and L is a divalent linking group. L is preferably a divalent organic group such as an alkylene group or an oxyalkylene group.

[0141] Preferred examples of L include -OC2H4-, -OC3H6-, -OCH2CH(CH3)-, -OC4H8-, -OC6H 12 -、-OC2H4-COO-C5H 10 -, one of which is connected to 2 to 10 linking groups (e.g. -(OC2H4) 10 -, etc.), wherein two or more connecting groups of 2 to 10 are connected (for example, -OC2H4-OC3H6-, etc.).

[0142] In the curable composition of the present embodiment, it is particularly preferred that the curable composition contain an acidic phosphoric acid compound in which n is 1 and an acidic phosphoric acid compound in which n is 2 in the general formula (A).

[0143] The acidic phosphoric acid compound represented by the general formula (A) can be purchased from, for example, Johoku Chemical CO., LTD. The acidic phosphoric acid compound represented by the general formula (A) can be synthesized by reacting phosphoric acid with a (meth)acrylate having a hydroxyl group in a side chain.

[0144] When the curable composition of the present embodiment contains the acidic phosphoric acid compound represented by the general formula (A), the amount thereof is preferably 0.1 to 10% by mass, more preferably 0.1 to 8% by mass, and further preferably 0.2 to 7% by mass in all non-volatile components of the curable composition.

[0145] (Other optional ingredients)

[0146] The curable composition of the present embodiment may contain any components other than those described above as long as sufficient performance can be obtained. Examples of the optional components include the following.

[0147] ·paraffin

[0148] When curing the curable composition, various paraffins can be used to rapidly cure the portion in contact with air. Examples of the paraffin include paraffin wax, microcrystalline wax, carnauba wax, beeswax, lanolin, spermaceti wax, ozokerite wax, and candelilla wax.

[0149] When the curable composition of the present embodiment contains paraffin wax, it may contain only one type of paraffin wax, or may contain two or more types of paraffin wax.

[0150] When the curable composition of the present embodiment includes paraffin wax, the amount thereof is preferably 0.01 to 3 parts by mass, more preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of the polymerizable monomer. By using a large amount of paraffin wax to a certain extent, the effect of rapid curing can be fully obtained. On the other hand, by not using too much paraffin wax, sufficient adhesion can be obtained, and the effect of rapid curing can be obtained.

[0151] Stabilizer

[0152] In order to improve storage stability, various stabilizers can be used. Examples of the stabilizer include (i) compounds known as phenolic antioxidants, such as 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), (ii) quinone compounds, such as p-benzoquinone and hydroquinone monomethyl ether, (iii) compounds known as polymerization inhibitors, such as amine polymerization inhibitors such as phenothiazine, citric acid, and (iv) stable free radical compounds having stable free radicals.

[0153] When the curable composition of the present embodiment contains a stabilizer, the composition may contain only one type of stabilizer or two or more types of stabilizers.

[0154] When the curable composition of the present embodiment contains a stabilizer, the amount thereof is, for example, 0.001 to 5 parts by mass, preferably 0.001 to 3 parts by mass, more preferably 0.01 to 1.5 parts by mass, and further preferably 0.02 to 1 part by mass, relative to 100 parts by mass of the polymerizable monomer.

[0155] ·Fluorescent agent

[0156] In particular, when the curable composition is used as an adhesive, in order to accurately grasp the position on the surface of the adherend where the curable composition is applied, the curable composition preferably contains a fluorescent agent. As the fluorescent agent, preferably, a compound that emits light by irradiation with ultraviolet rays can be mentioned. Specifically, coumarin derivatives, Azoles, stilbene derivatives, imidazole derivatives, triazole derivatives, rhodamine, etc. As commercially available fluorescent agents, Kayalight series (manufactured by Nippon Kayaku Co., Ltd.), Hakkol series (manufactured by SHOWA KAGAKU KOGYO CO., LTD.), rhodamine B (manufactured by FUJIFILM Wako Pure Chemical Corporation), etc. can be cited. As fluorescent agents, it is preferred to select substances that do not react with other components in the curable composition. In this embodiment, coumarin derivatives and / or Azole derivatives. Examples of coumarin derivatives include "Hakkol P" (manufactured by SHOWA KAGAKU KOGYOCO., LTD.).

[0157] When the curable composition of the present embodiment contains a fluorescent agent, the composition may contain only one fluorescent agent or two or more fluorescent agents.

[0158] In the case where the curable composition of the present embodiment includes a fluorescent agent, the amount thereof is preferably 0.001 to 5 parts by mass, more preferably 0.005 to 1.0 parts by mass, further preferably 0.008 to 0.5 parts by mass, and particularly preferably 0.01 to 0.3 parts by mass relative to 100 parts by mass of the polymerizable monomer. By using a large amount of fluorescent agent to a certain extent, it is easy to fully confirm the coating condition of the curable composition on the adherend. On the other hand, by not using too much fluorescent agent, the effect of the fluorescent agent can be obtained while maintaining other properties such as adhesion.

[0159] Spacer

[0160] The curable composition of the present embodiment may contain spacers in order to adjust the film thickness during use. Spacers are typically spherical particles made of a resin such as polyolefin. Spacers are sometimes also called "beads."

[0161] When a spacer is used, the amount thereof is preferably 0.1 to 3% by mass, more preferably 0.2 to 2% by mass, based on all nonvolatile components in the curable composition, from the viewpoint of obtaining the film thickness adjustment effect and obtaining strong adhesive force.

[0162] (Single dose / Double dose)

[0163] The curable composition of the present embodiment may be a so-called one-component type, or may be a two-component type, that is, a type in which two components filled in different containers are mixed immediately before use.

[0164] In the case of a two-part type, the polymerization initiator is preferably contained in the first part, and the reducing agent is preferably contained in the second part. However, the free radical polymerization initiator is preferably contained in the first part but not in the second part, and the reducing agent is preferably contained in the second part but not in the first part. By setting the first part and the second part in this way, it is easy to prevent an unexpected reaction or deterioration of the curable composition before mixing, and after mixing the first part and the second part, curability (adhesion) can be exhibited at a relatively low temperature near room temperature.

[0165] Incidentally, when the curable composition of the present embodiment is a two-part type, it is preferred that the amount of each component in the first part and the second part be adjusted so that the curable composition after mixing the first part and the second part contains each component within the range of the preferred content of each component described above. In addition, various properties of the curable composition described in this specification relate to the curable composition after mixing the first part and the second part when the curable composition is a two-part type.

[0166] (Various characteristics)

[0167] As described above, the polymerizable composition of the present embodiment is considered to exhibit good curing due to the synergistic effect of containing the azole compound and suppressing the intrusion of water into the cured product.

[0168] The “intrusion of water into the cured product is suppressed” can also be evaluated by an index other than the water absorption rate.

[0169] For example, the water contact angle of the surface of the cured product is believed to be related to the ability of water to hardly penetrate into the interior of the cured product. In other words, it is believed that a curable composition that can produce a cured film with a relatively large surface water contact angle can fully suppress the penetration of water that can reduce the adhesive strength.

[0170] Specifically, the water contact angle of the surface of the cured film of the curable composition of the present embodiment is preferably 80 to 90°. Here, the same cured film for testing used in the measurement of water absorption can be used for measuring the water contact angle of the cured film.

[0171] As another example, the wetting tension of the cured product surface is considered to be related to the degree to which water is difficult to penetrate into the cured product. In other words, a curable composition that can obtain a cured film with appropriately controlled wetting tension on the surface is considered to be a preferred aspect in this embodiment.

[0172] Specifically, the surface wetting tension of the cured film of the curable composition of the present embodiment is preferably 25 to 40 mN / m, more preferably 30 to 40 mN / m. Here, in measuring the wetting tension of the cured film, the same cured film for testing used in measuring water absorption can be used.

[0173] In addition, as another example, when the mechanical properties of the cured product of the curable composition change little before and after being immersed in water, it can be interpreted that the penetration of water into the cured product is suppressed, or even if water penetrates into the cured product, the degradation of the cured product is suppressed. In other words, by using a curable composition that can form a cured product with little change in mechanical properties before and after being immersed in water as an adhesive, good bonding strength can be obtained for a long time.

[0174] Specifically,

[0175] A 1BA dumbbell prepared by curing the curable composition at 23° C. for 24 hours was used as a sample, and the elongation at break in a tensile test at 23° C. at a tensile speed of 5 mm / min was defined as L1 (%).

[0176] A 1BA type dumbbell prepared by curing the curable composition at 23°C for 24 hours was immersed in pure water at 23°C for 24 hours, taken out of the water, and then cured for 1 hour in an environment of 23°C and 50RH%. The dumbbell was used as a sample, and the elongation at break when a tensile test was performed at 23°C at a tensile speed of 5 mm / min was defined as L2 (%).

[0177] The value of L2 / L1 is preferably 0.7 to 1.5, more preferably 0.7 to 1.0.

[0178] The tensile test for determining the above L1 and L2 is preferably performed in accordance with JIS K 7161-1: 2014. In addition, "1BA type dumbbell" means a small dumbbell 1BA shape specified in JIS K 7161-2: 2014.

[0179] (use)

[0180] As described above, the curable composition of the present embodiment is preferably used as an adhesive. That is, the curable composition of the present embodiment is preferably used to bond the first member and the second member.

[0181] The curable composition of this embodiment is preferably curable without heating (at room temperature) to bond articles (especially when a polymerization initiator and a reducing agent are included). Of course, heating is not excluded when bonding articles.

[0182] (Method for producing curable composition)

[0183] The curable composition of the present embodiment can be produced by mixing the above-mentioned components. As for the specific method of mixing, a known technique can be appropriately used. For example, the curable composition can be produced by uniformly mixing the components using a stirring blade.

[0184] <Cured products and bonded products (articles)>

[0185] A cured product can be obtained by curing the curable composition of the present embodiment. Specifically, by using the curable composition of the present embodiment as an adhesive, an adhesive body (article) including a first component, a second component, and a cured product of the curable composition bonding the first component and the second component can be obtained.

[0186] The material of the first component and the second component can be any material such as iron, non-ferrous metal, resin (plastic), etc. respectively. The material of the first component and the second component can be the same type or different types. From the viewpoint of exerting the characteristics of the curable composition of the present embodiment, the material of at least one of the first component and the second component is preferably iron or non-ferrous metal. The curable composition of the present embodiment is particularly preferably used for bonding metal parts that have been treated with zinc chromate. Here, for the sake of convenience, "zinc chromate treatment" is explained, and zinc chromate treatment refers to that the surface of the bulk metal is first zinc-plated, and the exposed surface of the zinc plating is further treated with chromate.

[0187] The curable composition of this embodiment is particularly preferably used for bonding metal parts in a speaker. The speaker vibrates when in use, so a sufficiently strong bonding force is required for the adhesive. In addition, since the speaker is used for a long time, it is preferred to suppress the decrease in bonding force for a long time. The curable composition of this embodiment has such a preferred characteristic and is preferably used for bonding metal parts in a speaker.

[0188] The curable composition of the present embodiment preferably gradually cures at room temperature without heating. Specifically, curability can be adjusted by adjusting the type or amount of the radical polymerization initiator, the type or amount of the reducing agent, and the like.

[0189] Although it is an example, after the curable composition is applied to the adherend, at room temperature (23°C), the time required for obtaining sufficient bonding strength is preferably 2 minutes to 1 hour, more preferably 2 to 30 minutes, and further preferably 2 to 20 minutes. The time until sufficient bonding strength is obtained is relatively long to a certain extent, so even if there is a change in the time from the application of the curable composition to the bonding, a certain bonding strength can be obtained. This property is a preferred property when bonding a large number of items in a flow operation. In addition, the time until the bonding strength is manifested will not be too long to improve production efficiency.

[0190] The embodiments of the present invention are described above, but these are examples of the present invention, and various structures other than the above can be adopted. In addition, the present invention is not limited to the above embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are included in the present invention.

[0191] Example

[0192] The embodiments of the present invention will be described in detail based on examples and comparative examples. However, the present invention is not limited to the examples.

[0193] <Preparation of curable composition>

[0194] The curable compositions (the first and second agents) of the embodiments and comparative examples were prepared by uniformly mixing the components shown in the table listed below. Specifically, the components shown in the table were weighed and put into a 1L stainless steel flask. A stainless steel anchor stirring blade was placed in the flask, and a three-in-one motor "BL300" made by Shinto Scientific Co., Ltd. was used to stir at 150 rpm for 24 hours to obtain a uniform viscous liquid.

[0195]

[0196]

[0197]

[0198] Incidentally, "EBECRYL 3708" used as epoxy acrylate is difunctional. "Epoxy Ester 3000M" used as epoxy methacrylate is difunctional. "JPA-514" (Johoku Chemical CO., LTD), an ester of phosphoric acid and hydroxyethyl methacrylate used as an acidic phosphoric acid compound, is a mixture of an acidic phosphoric acid compound having a chemical structure represented by the aforementioned general formula (A) and n being 1 and an acidic phosphoric acid compound having n being 2. In "JPA-514" in the aforementioned general formula (A), R is a methacryloyl group.

[0199] <Preparation of test cured film>

[0200] A test cured film of 50 mm×10 mm×1 mm was prepared in the following manner under an environment of 23° C. and 50 RH%. Incidentally, a plurality of test cured films were prepared for each curable composition of each Example / Comparative Example in order to perform various measurements a plurality of times.

[0201] (1) The center of a 1 mm thick silicone sheet was punched into a 50 mm×50 mm square to prepare a silicone sheet mold.

[0202] (2) The silicone sheet mold prepared in the above (1) was placed on a PET film (LUMIRROR 188 μm manufactured by TORAY INDUSTRIES, INC.).

[0203] (3) The double-barreled syringe was filled with the first and second agents of the two-component curable composition. The first and second agents were mixed in equal amounts by a static mixer and then ejected into the silicone sheet mold. Immediately after ejection, another PET film (LUMIRROR 188 μm manufactured by TORAY INDUSTRIES, INC.) was covered from above, sandwiched between two smooth glass plates, and a 500 g weight was placed from above. Thereafter, the mixture was cured at 23°C and 50 RH% for 24 h.

[0204] (4) After curing, the cured product was taken out from the silicone sheet mold and the burrs of the cured product were removed to prepare a test cured film.

[0205] <Measurement of water absorption of test cured film>

[0206] The measurement was performed by the following steps: The measurement was performed three times, and the average value of the water absorption obtained in each measurement was recorded as the water absorption in the table listed below.

[0207] (1) The mass W0 of the test cured film was measured.

[0208] (2) The test cured film was immersed in a beaker containing a sufficient amount of pure water and allowed to stand at 23° C. for 1 week.

[0209] (3) The test cured film was taken out from the beaker, and the water adhering to the surface was wiped off. Thereafter, the mass W1 of the test cured film was measured.

[0210] (4) The water absorption (%) was calculated using the formula {(W1-W0) / W0}×100.

[0211] <Measurement of water contact angle on the surface of the test cured film>

[0212] The water contact angle was measured in the following manner.

[0213] (1) A test cured film or device used for measurement was left to stand in an environment of 23° C. and 50% RH for 24 hours.

[0214] (2) The surface of the test cured film was wiped with a wipe cloth containing pure water. Within 5 minutes after wiping, the following (3) was performed.

[0215] (3) The contact angle was measured by the drop method and the θ / 2 method using a dynamic contact angle meter. Specifically, 2 μL of pure water manufactured by FUJIFILM WakoPure Chemical Corporation was dropped onto the surface of the test cured film using a device equipped with a DM500 manufactured by Kyowa Interface Science Co., Ltd. and a 18G Cateran needle manufactured by Kyowa Interface Science Co., Ltd.

[0216] (4) After pure water was dropped, the contact angle was measured 1 second later.

[0217] (5) The contact angle was measured 10 times at different locations of the test cured film, and the average value of the 10 values ​​obtained was recorded in the table listed below.

[0218] <Measurement of wetting tension of the surface of the test cured film>

[0219] The wetting tension of the surface of the test cured film was measured as follows. This time, as a wetting tension measurement reagent, wetting tension test mixed solution No. 30 to 55 manufactured by FUJIFILM Wako Pure Chemical Corporation was used as it is. A new cotton swab was used in each test. In addition, the measurement was performed three times, and the average value of the three values ​​obtained was recorded in the table listed below.

[0220] Hereinafter, for the sake of convenience, the measurement procedure is described in detail, but the following steps are not special steps and are common steps in the measurement of wetting tension using the mixed solution for wetting tension test.

[0221] (1) A test cured film or device used for measurement was left to stand in an environment of 23° C. and 50% RH for 24 hours.

[0222] (2) The surface of the test cured film was wiped with a wipe cloth containing pure water, and the following (3) was performed within 5 minutes after the wiping.

[0223] (3) Add a few drops of the mixed liquid for wetting tension test of any number onto the surface of the test cured film and spread it with a cotton swab. Observe the state of the liquid film 2 seconds after spreading, as shown below.

[0224] The state when the liquid film remains applied for more than 2 seconds without breaking is considered wet. Therefore, if the wetness is maintained for more than 2 seconds, the mixed liquid for the wetting tension test with a higher number is further introduced. On the contrary, if the liquid film breaks in less than 2 seconds, the mixed liquid for the wetting tension test with a lower number is then introduced.

[0225] (4) Repeat the operation of (3) above to select a mixed liquid for wetting tension test that can accurately wet the surface of the test piece within 2 seconds. At this time, the No. of the mixed liquid for wetting tension test that can accurately wet the surface of the test piece within 2 seconds becomes the wetting tension of the sample. For example, when the mixed liquid No. 40 for wetting tension test can accurately wet the surface of the test piece within 2 seconds, the wetting tension of the sample is 40.0 mN / m.

[0226] <Measurement of elongation at break of cured film (before and after water immersion)>

[0227] The measurement was performed by the following steps.

[0228] (1) Referring to JIS K 7161-2:2014, the curable composition was cured at 23° C. for 24 hours to prepare a 1BA type dumbbell. Incidentally, in order to perform multiple measurements, multiple dumbbells were prepared for each of the curable compositions of Examples / Comparative Examples.

[0229] (2) Using the dumbbell obtained in (1) above, a tensile test was performed under the conditions of 23°C, a tensile speed of 5 mm / min, and a chuck distance of 58 mm with reference to JIS K 7161-1:2014. The value of the elongation at break was obtained. The test was performed three times, and the average value of the three times was taken as the elongation at break L1 (%) and recorded in the table listed below.

[0230] (3) The dumbbell obtained in the above (1) was immersed in pure water at 23°C for 24 hours and taken out of the water. Thereafter, it was cured for 1 hour in an environment of 23°C and 50RH%. Using the dumbbell thus obtained, a tensile test was carried out with reference to JIS K 7161-1:2014 at 23°C, a tensile speed of 5mm / min, and a chuck spacing of 58mm. And the numerical value of the elongation at break was obtained. The test was carried out 3 times. And the average value of the 3 times was recorded as the elongation at break L2 (%) in the table listed later.

[0231] (4) The value of L2 / L1 was calculated.

[0232] <Performance evaluation: Basic characteristics as an adhesive>

[0233] (Coagulation time)

[0234] Evaluation was performed to confirm that the curable composition of each example was sufficiently and quickly cured at room temperature by the following procedure.

[0235] In an environment of temperature 23°C and humidity 50%, the first and second agents of the curable composition were mixed in equal amounts using a static mixer and applied to one side of a test piece (100 mm × 25 mm × 1.6 mm, sandblasted iron plate) in accordance with JIS K 6850: 1999. Immediately thereafter, another test piece (100 mm × 25 mm × 1.6 mm, sandblasted iron plate) was overlapped and laminated to serve as a sample for setting time measurement.

[0236] The setting time (unit: minute) of the sample was evaluated at a temperature of 23° C. and a humidity of 50% from immediately after coating using a push-pull dynamometer (Model S, manufactured by Komura Co., Ltd.). Specifically, the time until an adhesive strength of 0.39 [MPa / 3.125] or more was achieved by evaluation using a push-pull dynamometer and a stopwatch was defined as the setting time.

[0237] (Adhesion strength: tensile shear test)

[0238] The following procedures were used to evaluate whether the curable composition of each example could sufficiently firmly bond to an adherend and had basic performance as an adhesive.

[0239] In an environment of temperature 23°C and humidity 50RH%, according to JIS K 6850:1999, the first and second agents of the curable composition were mixed in equal amounts using a static mixer and applied to one side of a test piece A (thickness and material will be described later). Immediately thereafter, the test piece B (thickness and material will be described later) was overlapped and laminated, and the test piece cured for 24 hours in the same atmosphere was used as a measurement sample. The tensile shear bond strength of the test sample was measured at a tensile speed of 10mm / min. at a temperature of 23°C and a humidity of 50%.

[0240] In order to evaluate the adhesiveness to various materials, test specimens were prepared using the following three combinations of test piece A / test piece B: (i) to (iii). Each of (i) to (iii) was measured three times, and the average value of the three measurements was taken as the tensile shear adhesive strength.

[0241] (i) Test piece A: SPCC-SD (oil surface) / Test piece B: SPCC-SD (oil surface)

[0242] JIS G 3141, 100mm×25mm×1.6mmt, Test piece Co., Ltd.

[0243] (ii) Test piece A: AL5052P (oil surface) / Test piece B: AL5052P (oil surface)

[0244] JIS H 4000, 100mm×25mm×2.0mmt, Test piece Co., Ltd.

[0245] (iii) Test piece A: polycarbonate PANLITE L-1225Y / Test piece B: polycarbonate PANLITE L-1225Y ("PANLITE" is a registered trademark)

[0246] 100mm×25mm×2.0mmt, Test piece Co., Ltd.

[0247] <Performance evaluation: Changes in the adhesion of metal materials over time>

[0248] By the following procedure, changes in adhesive strength over time when each curable composition was used as an adhesive to bond a metal material were evaluated.

[0249] In an environment of temperature 23°C and humidity 50%, according to JIS K 6850:1999, the first and second agents of the curable composition were mixed in equal amounts using a static mixer and applied to one side of a zinc chromate plated test piece. Immediately thereafter, a SUS304 sandblasted test piece was overlapped and bonded, and cured for 24 hours in the same atmosphere, and used as a measurement sample. In order to perform the following evaluation over time, a plurality of measurement samples (a minimum of 9 for each example) were prepared.

[0250] The tensile shear bond strength of the test sample was measured at a tension rate of 10 mm / min. in an environment of 23° C. and 50% humidity. The measurement was performed three times, and the average of the three values ​​obtained was taken as the tensile shear bond strength.

[0251] Here, as the zinc chromate plating test piece, a JIS G 3144 (SPCC, SB) zinc chromate plating 3-5 μm treatment (trivalent chromium), 100 mm×25 mm×1.6 mmt, manufactured by Test Piece Co., Ltd. was used.

[0252] The test sample was stored at 85°C and 95 RH% for 120 hours, and the tensile shear bond strength was measured under the same conditions as above. The measurement was performed three times, and the average of the three values ​​obtained was taken as the tensile shear bond strength.

[0253] Furthermore, the test sample was stored at 85°C and 95 RH% for 240 hours, and the tensile shear bond strength was measured under the same conditions as above. The measurement was performed three times, and the average of the three values ​​obtained was taken as the tensile shear bond strength.

[0254] The above-mentioned measurement / evaluation results are summarized in the table listed below.

[0255] Table 4

[0256]

[0257] Table 5

[0258]

[0259] Table 6

[0260]

[0261] As shown in the table above, in the evaluation using the curable composition of the Examples containing an azole compound and having a water absorption of 1.5 to 3.6% when formed into a cured film, the decrease in adhesive strength over time (accelerated test at 85°C and 95 RH%) was suppressed.

[0262] On the other hand, in the evaluation of the curable compositions of Comparative Examples containing an azole compound but having a water absorption of less than 1.5% or more than 3.6% when formed into a cured film, the adhesive force significantly decreased over time (accelerated test at 85°C and 95 RH%).

[0263] <Observation of corrosion on metal (zinc chromate plating) surface>

[0264] After the tensile shear bond strength was measured in the above, the zinc chromate plated test piece (the test piece was stored at 85° C. and 95 RH % for 240 hours before the measurement) was visually observed for the presence or absence of corrosion on the surface of the test piece.

[0265] As a result of the observation, corrosion (rust) was observed on the portion of the test piece surface coated with the curable composition in Examples 2 to 5. On the other hand, corrosion (rust) was not observed on the portion of the test piece surface coated with the curable composition in Examples 1 and 6 to 12.

[0266] The above results are considered to indicate that the corrosion of a metal adherend can be highly suppressed depending on the type and amount of the azole compound.

[0267] This application claims priority based on Japanese Patent Application No. 2022-133920 filed on August 25, 2022, and all disclosed contents thereof are incorporated herein.

Claims

1. A curable composition comprising a polymerizable monomer having a carbon-carbon double bond, a free radical polymerization initiator, an azole compound, an elastomer and a reducing agent, wherein: The curable composition was sandwiched between two PET films and cured at 23°C for 24 hours to obtain a 50 mm×10 mm×1 mmt test cured film. The test cured film was immersed in pure water at 23°C for one week and had a water absorption of 1.5 to 3.6%.

2. The curable composition according to claim 1, wherein The polymerizable monomer includes a (meth)acrylic monomer.

3. The curable composition according to claim 1 or 2, wherein The polymerizable monomer includes a monofunctional (meth)acrylic monomer.

4. The curable composition according to claim 1 or 2, wherein The polymerizable monomer includes epoxy (meth)acrylate.

5. The curable composition according to claim 1 or 2, wherein The ratio of the monomer having two or more carbon-carbon double bonds in one molecule is 0 to 10% by mass in the entire polymerizable monomers.

6. The curable composition according to claim 1 or 2, wherein The elastomer includes at least one selected from the group consisting of ABS-based resin and nitrile rubber.

7. The curable composition according to claim 1 or 2, further comprising an acidic phosphoric acid compound represented by the following general formula (A), In the general formula (A), When there are a plurality of R, each R is independently a group containing a (meth)acryloyl group, n is 1 or 2.

8. The curable composition according to claim 7, wherein In the general formula (A), an acidic phosphoric acid compound in which n is 1 and an acidic phosphoric acid compound in which n is 2 are included.

9. The curable composition according to claim 1 or 2, wherein The azole compound includes at least any one selected from the group consisting of benzotriazole and tolyltriazole.

10. The curable composition according to claim 1 or 2, wherein The reducing agent comprises thiourea or a derivative thereof.

11. The curable composition according to claim 1 or 2, wherein The water contact angle of the surface of the test cured film was 80 to 90°.

12. The curable composition according to claim 1 or 2, wherein A 1BA dumbbell prepared by curing the curable composition at 23° C. for 24 hours was used as a sample, and the elongation at break when a tensile test was performed at 23° C. at a tensile speed of 5 mm / min was defined as L1 (%). A 1BA type dumbbell prepared by curing the curable composition at 23°C for 24 hours is immersed in pure water at 23°C for 24 hours, taken out of the water, and then cured for 1 hour in an environment of 23°C and 50RH%. The dumbbell is used as a sample, and when the elongation at break during a tensile test at 23°C and a tensile speed of 5 mm / min is set to L2 (%), the value of L2 / L1 is 0.7 to 1.

5.

13. The curable composition according to claim 1 or 2, wherein The curable composition is a two-component curable composition consisting of a first component and a second component, which are mixed immediately before use. The first agent includes the radical polymerization initiator, and the second agent includes the reducing agent.

14. The curable composition according to claim 1 or 2, which is used as an adhesive.

15. A cured product, which is a cured product of the curable composition according to claim 1 or 2.

16. An article comprising the cured product according to claim 15.

Citation Information

Patent Citations

  • Biological information calculation system

    JP2022133920A